Sex and stature estimations from dry femurs of Northeastern Thais: Using a logistic and linear regression approach - Worrawit Boonthai; Chanasorn Poodendaen; Juthamas Kamwong; Piyanan Sangchang; Suthat Duangchit; Sitthichai Iamsaard (Translational Research in Anatomy)
Background: Sex determination and stature estimation from skeletal remains are still crucial components in creating biological profiles in forensic anthropology. The femur is particularly valuable due to its high sexual dimorphism and correlation with stature. This study aimed to develop sex estimation models and stature reconstruction equations using femoral measurements in a Northeastern Thai population. Materials and method: The 400 dry femora were measured for its six parameters including femur maximum length (FL), femoral shaft length (FSL), femur epicondylar breadth (FEB), femur maximum head diameter (FHD), femur midshaft circumference (FMC) and femur weight (FW). Then all parameters were analyzed by using logistic regression for sex estimation and linear regression for stature reconstruction. Results: Results showed significant sexual dimorphism across all measured parameters, with FHD being the best predictor of sex (correction rate, 88.5 %). The optimized multivariate model achieved the highest accuracy (91.0 %). For stature estimation, sex-specific equations demonstrated superior accuracy compared to combined-sex models. The FL and FSL showed the strongest correlations with stature. Conclusion: This study demonstrated the importance of population-specific standards in forensic anthropology of the femur's reliability as a valuable tool for both sex determination and stature estimation. These results contribute significantly to forensic practice in Thailand, enhancing the accuracy of biological profile reconstruction in medicolegal investigations.